HUBUNGAN PENGETAHUAN DAN SIKAP IBU POST SEKSIO CAESAREA TERHADAP PERAWATAN LUKA SEKSIO CAESAREA - Sri Dewi Br Siregar; Jesmo Aldoran Purba (KOLONI, 2022)
Cesarean section is surgery to deliver the fetus by opening the abdominal wall and uterine wall. Surgical assistance in childbirth is an action to save both the mother and the baby. According to the WHO definition, maternal death is the death of a woman pregnant or after the termination of pregnancy from any cause. The number obtained for maternal deaths in 2016 in developed countries generally ranged between 1.5 and 3.0 per 10,000 live births and in 2017 maternal deaths were 3.2 people per year. This study aimed to identify the relationship between knowledge and attitudes of mothers after cesarean section to care for cesarean section wounds. The type of quantitative research with the design used in this research is a descriptive correlation with a cross-sectional approach. In the research population of post-sectional cesarean mothers at Estomihi Hospital Medan, the number of samples used in this study was 57 people. Non-probability sampling is a purposive sampling technique. Data analysis used a univariate test and bivariate analysis with Spearman Rank (Rho) correlation test. The results of the correlation coefficient there is no significant relationship between mother's knowledge and management of cesarean section wound care with a p-Value < (0.532> 0.05), there is a significant relationship between mother's attitude and management of Caesarean section wound care with p-Value < (0.007< 0.05). It is hoped that this research can be used as a reference regarding post-cesarean section nursing care for cesarean section wound care in hospitals so that later it will improve the quality of service at the hospital. Keywords: Knowledge, Attitude, Implementation, Caesarean section